MODELS OF DEVELOPMENT OF COGNITIVE INTEREST IN THE STUDY OF GEOGRAPHY IN SENIOR PROFILE SCHOOL (Pedagogy of Higher and Secondary Education, 2011)
In article features and problems of studying of geography at the senior profile school are considered, models of development of informative interest to geography in classes of a various profile are presented.
Keywords: profile training; informative interest